Smart Wires and Modular FACTS Controllers for Smart Grid Applications: A Review - Bhatt, Pramod Kumar (Journal of Electrical Engineering and Automation, 2022)
Flexible AC Transmission System (FACTS) controller has got unanimous acceptance in the electric power industry due to their power control capability especially in transmission and sub transmission networks. These FACTS devices play a decisive role in stability enhancement and effective asset utilization. The controllers suffer from grave drawbacks such as colossal size, poor reliability, high cost, and unavailability of experienced personnel for operation and maintenance, which makes them unapt to be used in smart grid and modern power system applications. These inadequacies are effectively assuaged by the distributed FACTS devices, which are proliferated along the transmission lines, are said to be portable, cost-effective, highly reliable, and easy to maintain. This paper explores an exhaustive review of the smart wires and modular FACTS controllers with their application in smart power networks.